Penerapan Personal Hygine Pada Pasien Diruang Icu Rumah Sakit Tk III Dr R Soeharsono Banjarmasin - ., Ernawati; Ariani, Sri Purwanti (CV. ITTC INDONESIA, 2024)
Nursing care is an important aspect of healthcare in achieving patient satisfaction. One of the nursing skills that can influence patient satisfaction is the fulfillment of patients' personal hygiene needs. This research aims to determine the relationship between personal hygiene by nurses in the ICU Ward of Dr. R. Soeharsono Hospital in Banjarmasin. The research design is descriptive analytical with a cross-sectional approach. The population consists of all physically immobilized patients in the Inpatient Ward of Dr. R. Soeharsono Hospital in Banjarmasin